2022
DOI: 10.3390/en15020561
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Laboratory Evolution for Multistress Tolerance, including Fermentability at High Glucose Concentrations in Thermotolerant Candida tropicalis

Abstract: Candida tropicalis, a xylose-fermenting yeast, has the potential for converting cellulosic biomass to ethanol. Thermotolerant C. tropicalis X-17, which was isolated in Laos, was subjected to repetitive long-term cultivation with a gradual increase in temperature (RLCGT) in the presence of a high concentration of glucose, which exposed cells to various stresses in addition to the high concentration of glucose and high temperatures. The resultant adapted strain demonstrated increased tolerance to ethanol, furfur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 42 publications
(63 reference statements)
0
4
0
Order By: Relevance
“…The mutant somehow kept a lower level of acetate compared to the other adapted mutants as seen in the medium containing 160 g L −1 of glucose at 40 • C to 45 • C. Notably, K. marxianus DMKU 3-1042 as well as adapted strains exhibited a stronger resistance to high temperatures (up to 48 • C) on agar plates [16]. It is assumed that only the surface cells of colonies on agar plates are exposed to oxidative stress, which increases with rising temperature [47], and individual cells in liquid media are directly exposed to the stress. The thermal stability of K. marxianus DMKU 3-1042 is one of the most important application criteria for different applications, and this property is crucial for the preparation strategy of the strain or its stabilization.…”
Section: Discussionmentioning
confidence: 99%
“…The mutant somehow kept a lower level of acetate compared to the other adapted mutants as seen in the medium containing 160 g L −1 of glucose at 40 • C to 45 • C. Notably, K. marxianus DMKU 3-1042 as well as adapted strains exhibited a stronger resistance to high temperatures (up to 48 • C) on agar plates [16]. It is assumed that only the surface cells of colonies on agar plates are exposed to oxidative stress, which increases with rising temperature [47], and individual cells in liquid media are directly exposed to the stress. The thermal stability of K. marxianus DMKU 3-1042 is one of the most important application criteria for different applications, and this property is crucial for the preparation strategy of the strain or its stabilization.…”
Section: Discussionmentioning
confidence: 99%
“…One interesting aspect of ALE is the occurrence of multiple evolved phenotypes, as an indirect result of a particular directed evolution towards a certain goal. For example, Phommachan et al [ 66 ], aimed to use strains of Candida tropicalis to improve their resistance to high glucose concentrations. After long-term cultivation with increasing temperatures (40 °C to 44.5 °C) and the periodical transfer of evolved cultures to media with high glucose concentrations, authors obtained strains that, in addition to fermenting high glucose concentrations, also showed increased tolerance to ethanol, furfural, and hydroxymethylfurfural at high temperatures, and improved xylose-fermenting ability.…”
Section: Evolution Of Non-conventional Yeast Species Through Alementioning
confidence: 99%
“…Phommachan et al reported ALE-evolved strains of Candida tropicalis showing tolerance to multiple stress [ 75 ]. They isolated the C. tropicalis strain in Laos, which is a thermotolerant xylose-fermenting yeast, but this species shows sensitivity to a high concentration of glucose.…”
Section: Acquisition Of Stress Tolerance To Microorganisms With Alementioning
confidence: 99%